THE EFFECT OF PARAPHRASING ON EFL STUDENTS' WRITING AT INDONESIAN HIGHER EDUCATION - Rafiqa, Rafiqa; Pabbajah, M. Taufiq Hidayat; Asfihana, Raida; Naazaruddin, Rezkiawati; Latifah, Latifah (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
The paper intends to enquire about the effectiveness of paraphrasing in evolving the EFL students' writing ability for Indonesian Higher Education. The study was quasi-experimental research, and it was conducted in the 4th semester of the English students at Universitas Sulawesi Barat. The research instrument was a writing test, and the student’s scores were gathered through paraphrasing rubric scores. Statistical inferential analysis was performed on the data. It is possible to conclude that The Ha (Alternative) Hypothesis was established hence the paired samples test result carried out with SPSS performed that the sig. rating on the value obtained from the T-test was lower than Sig. value, so theory Y assumptions (Ha) were approved, and both the pilot testing and post-intervention results of the study demonstrated Sig. (2-tailed = 0.000) has been less than 0.05. In other words, this indicates that there is a consequence. The research finishes with pedagogical recommendations for trying to better the paraphrasing skills of novice student writers, and paraphrasing has a medium effect on the EFL students’ writing ability in Indonesian higher education.